Reproductive Health Literacy in Adolescent in Indonesia: a Scoping Review - Zulfa Mazida; Shrimarti Rukmini Devy; Rachmah Indawati (Indonesian Journal Publisher, 2026)
ABSTRACT Background: In Indonesia, discussions about reproductive health among adolescents remain constrained by cultural taboos, limited parental communication, and unequal access to accurate information, especially between urban and rural areas. These barriers contribute to low levels of reproductive health literacy. Purpose: This scoping review aims to identify the determinants influencing reproductive health literacy among Indonesian adolescents. Methods: A systematic search was conducted in Scopus, PubMed, and ProQuest databases on January 28, 2026, using Boolean operators with key terms such as